Surgical Management for Silicone Oil Barrier of Traumatic Aniridia with Aphakia: Suturing of Temporary Iris-Diaphragm Prior to Final Iris-Lens-Diaphragm Implantation - Mayer CS (Dove Medical Press, 2020)
Christian S Mayer,1,* Isabella Baur,1,* Julia Storr,2 Alexander Markard,1 Ramin Khoramnia1 1Department of Ophthalmology, University Hospital Heidelberg, University of Heidelberg, Heidelberg, Germany; 2Department of Ophthalmology, Technical University Munich, Munich, Germany*These authors contributed equally to this workCorrespondence:Christian S MayerDepartment of Ophthalmology, University Hospital Heidelberg, University of Heidelberg, Im Neuenheimer Feld 400, Heidelberg 69120, GermanyEmail Christian.Mayer@med.uni-heidelberg.dePurpose: Patients with traumatic aniridia, aphakia and retinal complications can require silicone oil endotamponade. In the absence of compartmentalization, there is a risk of silicone oil migrating to the anterior chamber which can cause long-term complications. We report a two-step procedure in trauma cases, using sutures for silicone oil retention in primary care and subsequently prior to secondary artificial iris (AI) and intraocular lens (IOL) implantation, to achieve a reconstruction of the anterior and posterior chamber.Material and Methods: Seven patients with loss of the iris-lens-diaphragm after an ocular trauma and the need for silicone oil endotamponade underwent a primary intervention including wound closure, placement of silicone oil retention sutures and silicone oil filling. Four of those underwent secondary reconstruction with silicone oil removal and AI and IOL implantation and could be included in this retrospective observational study. All main outcome measures were evaluated after the first and after the second surgery. The main outcome measures were morphological findings, subjective impairment from glare, subjective cosmetic disfigurement, patient satisfaction and intraocular pressure (IOP) as well as best-corrected distance visual acuity and objective refraction.Results: The retention sutures could effectively prevent silicone oil migration into the anterior chamber in the first surgery. Silicone oil emulsifications in the anterior chamber were observed in one patient. In two patients, pigment deposition at the sutures was seen. Subjective impairment from glare and subjective cosmetic disfigurement could be reduced after the second surgery compared to the evaluation after the first surgery. IOP and best-corrected distance visual acuity remained stable. No eye needed silicone oil refilling after the secondary reconstruction surgery.Conclusion: Our two-step approach is viable and provides good functional and aesthetic results. We observed a high patient satisfaction.Keywords: aniridia, aphakia, trauma, open globe injury, retinal detachment